Institutional Management Model for Research and Innovation in Higher Education Institutions in Latin America - Bernal Gamboa, Elizabeth; Granados Falla, Diana; Pallares, César; Marzal, Alfonso; Pallares, César; Díaz Ulloa, Claudia Milena; Granados Falla, Diana; Herrera Pérez, Eder Guillermo; Bernal Gamboa, Elizabeth; Colucci, Elizabeth; Vera López, Enrique; Ospina Rozo, Erika; et al. (UPTC Editorial, 2022)
The Institutional Management Model for Research and Innovation in Higher Education Institutions in Latin America is the result of the Erasmus+ Project, co-financed by the European Union, in which 20 universities, government entities, agencies and associations from Spain, Italy, Sweden, Colombia, Chile and Peru participated, called “Modernization of the Institutional Management of Research and Innovation in the Andean Region of Latin America - MIMIR Andino”. In this publication, the stages followed in the construction of the model are briefly presented, as well as its guiding principles and differential  elements. The model proposes a management that integrates four components: Strategic, Execution, Relational and Administrative. Reflections and suggestions are included in each of the components to be considered, adapted or applied, when deemed appropriate, within the framework of the institution’s autonomy, to improve its R&D&i management. Finally, a synthetic map of the model is included, as well as general recommendations and clues for its monitoring and implementation. It is suggested to use this model in conjunction with the Institutional Self-assessment Instrument for R&D&i Management MIMIR Andino, that can be found on the pages https://mimirandino.org and https://ascun.org.co.